Robust Model Predictive Control of a Benchmark Electromechanical System - Colombo Junior, Jose Roberto; Magalhaes Afonso, Rubens Junqueira; Harrop Galvao, Roberto Kawakami; Assuncao, Edvaldo [UNESP] (Springer, 2016)
This paper presents an experimental investigation concerning the use of robust model predictive control (RMPC) for a two-mass-spring system. This benchmark system has been employed as a numerical simulation example in several works involving RMPC formulations, but an actual experimental implementation has never been reported. Particular care was taken to solve the optimization problem with linear matrix inequalities within a small sampling period (15 ms). A discussion concerning the discretization of the uncertain model is presented to justify the use of the exact zero-order hold method. More specifically, the resulting loss of polytopic structure was found to be negligible with the adopted sampling period. Three experimental scenarios were considered, with different ranges for the uncertain spring stiffness coefficient. In all cases, the control task was successfully accomplished, with proper satisfaction of constraints on the input voltage and spring deformation.
Keywords: Predictive control; Robust control; Constrained control; Linear matrix inequalities; Two-mass-spring system